Long-term cultures of human pancreatic islets in self-assembling peptides hydrogels - Marchini, Amanda; Ciulla, Maria Gessica; Antonioli, Barbara; Agnoli, Alessandro; Bovio, Umberto; Visnoviz, Virginia; Bertuzzi, Federico; Gelain, Fabrizio (Frontiers in Bioengineering and Biotechnology, 2023)
Human pancreatic islets transplantation is an experimental therapeutic treatment for Type I Diabetes. Limited islets lifespan in culture remains the main drawback, due to the absence of native extracellular matrix as mechanical support after their enzymatic and mechanical isolation procedure. Extending the limited islets lifespan by creating a long-term in vitro culture remains a challenge. In this study, three biomimetic self-assembling peptides were proposed as potential candidates to recreate in vitro a pancreatic extracellular matrix, with the aim to mechanically and biologically support human pancreatic islets, by creating a three-dimensional culture system. The embedded human islets were analyzed for morphology and functionality in long-term cultures (14- and 28-days), by evaluating β-cells content, endocrine component, and extracellular matrix constituents. The three-dimensional support provided by HYDROSAP scaffold, and cultured into MIAMI medium, displayed a preserved islets functionality, a maintained rounded islets morphology and an invariable islets diameter up to 4 weeks, with results analogues to freshly-isolated islets. In vivo efficacy studies of the in vitro 3D cell culture system are ongoing; however, preliminary data suggest that human pancreatic islets pre-cultured for 2 weeks in HYDROSAP hydrogels and transplanted under subrenal capsule may restore normoglycemia in diabetic mice. Therefore, engineered self-assembling peptide scaffolds may provide a useful platform for long-term maintenance and preservation of functional human pancreatic islets in vitro.